The Effect of the CTL Learning Model on 5th Grade Student Learning Outcomes in the Pancasila Education Subject - Ni Putu Ayu Wanda Sukarmi; I Made Tegeh; Ni Wayan Eka Widiastini (Universitas Pendidikan Ganesha, 2025)
Pancasila Education learning in elementary schools still tends to be lecture- and memorization-oriented, thus failing to provide meaningful learning experiences and resulting in low student achievement. This study aims to analyze the effect of applying the Contextual Teaching and Learning (CTL) model on student learning outcomes in Pancasila Education. This study uses a quantitative approach with a quasi-experimental design in the form of a post-test only control group design. The research subjects involved the entire population of fifth-grade students who were randomly divided into two groups, namely the experimental group who received learning using the CTL model and the control group who received conventional learning. Data were collected through multiple-choice objective tests compiled based on Pancasila Education learning achievement indicators and had undergone expert validation as well as validity and reliability tests. Data analysis was performed using descriptive and inferential statistics, with tests of normality and homogeneity prerequisites, as well as hypothesis testing using independent sample t-tests. The results showed that the application of the CTL model had a positive and significant effect on student learning outcomes compared to conventional learning. Thus, the CTL model has implications as an alternative effective learning strategy in supporting the achievement of character education goals and meaningful learning in elementary schools.